Mutual Relationship of Islamic Law and Private International Law in Inheritance Matters - Khalifa, Attia Suleiman; Samad, Nashwan Salah (Indonesian Journal of Law and Economics Review, 2025)
General Background: In today’s globalized world, cross-border inheritance disputes are increasingly common, raising challenges where Islamic law intersects with private international law. Specific Background: Islamic inheritance rules, grounded in the Qur’an and Sunnah, impose mandatory shares, while private international law addresses conflicts of laws, jurisdiction, and recognition of foreign judgments. Knowledge Gap: Despite extensive literature on both systems, little research has focused on their mutual influence, particularly in reconciling religiously based inheritance rules with secular international frameworks. Aims: This study investigates how Islamic inheritance principles interact with private international law, highlighting areas of harmony and conflict, and exploring mechanisms for integration. Results: The analysis reveals significant challenges such as jurisdictional disputes, limits of testamentary freedom, procedural diversity, and the role of public order in excluding foreign laws. It also identifies opportunities for harmonization through bilateral agreements, renvoi application, and judicial adaptation. Novelty: Unlike previous works, this research provides a comparative approach supported by case studies, proposing models that respect both Islamic values and international legal norms. Implications: The findings suggest pathways to develop legal systems that uphold religious and cultural diversity while ensuring fairness, predictability, and global legal coherence in inheritance matters. Highlights: Interaction of Islamic inheritance principles with private international law creates both harmony and conflict. Public order plays a decisive role in accepting or rejecting foreign inheritance laws. Bilateral agreements and clear choice-of-law provisions help reduce cross-border disputes. Keywords: Islamic Law, Private International Law, Inheritance, Conflict of Laws, Cross Border Disputes